Data on Macrophyte cover and groundwater as the key drivers of the extremely high organic carbon concentration of soda pans - Csitári, Bianka (Uppsala University, 2019)
The soda pans of the Carpathian Basin present a wide variability of biotic and abiotic characteristics that provide an adequate system to assess the determinants of extreme high DOC concentrations. Here, we demonstrate through a multi‐site comparison, a multi‐year seasonal monitoring, and a laboratory experiment that the dissolved organic matter content of the highest DOC concentration soda pans is primarily of groundwater and emergent macrophyte origin.

The studied soda pans are located in the central area of the Carpathian Basin, on the interfluve area of the Danube and Tisza rivers. In the multi-site comparison, 14 natural pans were sampled between April and September of 2017 to assess the potential effect of groundwater and macrophytes on the organic matter content. The pans were selected in order to cover a broad range in respect of turbidity, CDOM and emergent macrophyte cover.

Samples were collected and transported to the lab for CDOM, DOC, TSS, and fluorescence excitation-emission matrix (EEM) spectroscopy (EEMS) measurement.

The dataset consists of seasonal monitoring data and fluorescence spectra used for the EEMS.

Please see manuscript "Macrophytes and groundwater drive extremely high organic carbon concentration of soda pans" by Boros et al (2020) for furhter information about the methods and study.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om datasetet och studien bakom.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on Macrophyte cover and groundwater as the key drivers of the extremely high organic carbon concentration of soda pans
Keywords: dissolved organic carbon; löst organiskt kol; groundwater; grundvatten; biochemistry; biokemi; Natural Sciences; Naturvetenskap